2022
DOI: 10.3390/gels8050322
|View full text |Cite
|
Sign up to set email alerts
|

Novel Acrylamide/2-Acrylamide-2-3 Methylpropanesulfonic Acid/Styrene/Maleic Anhydride Polymer-Based CaCO3 Nanoparticles to Improve the Filtration of Water-Based Drilling Fluids at High Temperature

Abstract: Filtration loss control under high-temperature conditions is a worldwide issue among water-based drilling fluids (WBDFs). A core–shell high-temperature filter reducer (PAASM-CaCO3) that combines organic macromolecules with inorganic nanomaterials was developed by combining acrylamide (AM), 2-acrylamide-2-methylpropane sulfonic acid (AMPS), styrene (St), and maleic anhydride (MA) as monomers and nano-calcium carbonate (NCC). The molecular structure of PAASM-CaCO3 was characterized. The average molecular weight … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 35 publications
0
11
0
Order By: Relevance
“…At the moment, the actual problems of drilling oil and gas wells are: Loss of circulation of the drilling flushing fluid [ 216 , 217 , 218 , 219 ]. Uncontrolled inflow of formation fluid into the well [ 220 ].…”
Section: Gels For Well Drillingmentioning
confidence: 99%
See 2 more Smart Citations
“…At the moment, the actual problems of drilling oil and gas wells are: Loss of circulation of the drilling flushing fluid [ 216 , 217 , 218 , 219 ]. Uncontrolled inflow of formation fluid into the well [ 220 ].…”
Section: Gels For Well Drillingmentioning
confidence: 99%
“… Swelling of clay rocks [ 223 , 224 ]. Thermal stability of the drilling flushing fluid [ 215 , 217 , 223 ]. Resistance of the drilling flushing fluid to aggressive environments.…”
Section: Gels For Well Drillingmentioning
confidence: 99%
See 1 more Smart Citation
“…Gels 2022, 8, 547 2 of 14 Fluid loss reducer, as one of the most essential additives in WBDFs, which can fully control the rheology and filtration performance of drilling fluids, has attracted extensive attention from petroleum engineering researchers in academia and industry [9][10][11][12]. The common fluid loss reducers are mainly divided into two categories: natural/natural-modified polymers and synthetic polymers, which can optimize the particle size distribution of bentonite particles and reduce the permeability of mud cakes, thereby achieving the effect of reducing drilling fluid filtration [13].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to conformance control agents, gels can also be used as additives in drilling fluids. Tang et al [ 5 ] reported novel nanoparticles (acrylamide/2-acrylamide-2-3 methylpropanesulfonic acid/styrene/maleic anhydride polymer-based nanoparticles), which can improve the filtration of water-based drilling fluids at a high temperature. The rheological properties of the drilling fluids that were treated with these nanoparticles were stable before and after aging at 200 °C/16 h and the filtration control was improved.…”
mentioning
confidence: 99%